Gender related differences in treatment and response to statins in primary and secondary cardiovascular prevention: The never-ending debate. (March 2017) - Cangemi, Roberto; Romiti, Giulio Francesco; Campolongo, Giuseppe; Ruscio, Eleonora; Sciomer, Susanna; Gianfrilli, Daniele; Raparelli, Valeria
Graphical abstract: Abstract: Statins are a main curbstone in the prevention of cardiovascular disease (CVD), pandemic in 21st century. CVD displays evident sex and gender differences, not only in clinical manifestation and outcomes but also in pharmacological treatment. Whether statin therapy should be differentially prescribed according to sex is a matter of debate. Aside a different pharmacological action, statins are not proven to be less effective in one gender comparing to the other, nor to be less safe. Nevertheless, up to date evidence shows that statins have not been adequately tested in women, especially in primary prevention trials. Since data-lacking, making a treatment decision on women is potentially harmful, although female individuals represent the majority of the population and they have a greater lifetime CVD risk. Therefore, adequately powered randomized control trials with longer follow-up are warranted to establish if a benefit on CV events and mortality prevention exists in both sexes. The aim of the present review is to summarize the sex and gender differences in statin use: it raises concerns and updates perspectives towards an evidence-based and sex-tailored prevention of CVD management.